Preliminary assessment of sediment transport and associated bacteriological contamination in a mountainous rural karst area (Sierra de Ubrique, S Spain) - Fernández-Ortega, Jaime; Barberá-Fornell, Juan Antonio; Andreo-Navarro, Bartolomé (Jaime Fernández Ortega, 2021)
Sierra de Ubrique is a karstified carbonate aquifer system developed in Jurassic limestones and dolostones located in one of the wettest regions in Spain (NE of Cádiz province). Groundwater discharge, which is mainly produced through three karst springs (Algarrobal and Cornicabra -permanent- and Garciago -overflow-), is also used for drinking water supply of Ubrique town (17,000 inhabitants). During flooding conditions, high turbidity events at the two permanent springs (up to 350 NTU) are simultaneous to maximum discharge, hindering the exploitation of groundwater for human consumption. This work aims to identify and characterize the main contamination sources and to understand the role of sediment transport in the occurrence of polluted groundwater episodes. For that purpose, a complete climate and groundwater monitoring network has been installed including a weather station and field devices for continuous record of physical-chemical parameters (discharge, electrical conductivity, water temperature, turbidity and tryptophan-like-fluorescence -TLF-). . The response times in output signals of the two main springs, maximum thresholds of pollutants and statistical correlations among specific chemical/bacteriological-like parameters lead to explain the main contaminant transport mechanisms, which greatly differ in the examined karst connections. Even though, the influence of the concentrated recharge is clear in both of the springs, as clayey sediments from the shaft catchment erosion and its remobilization from inside the system serve as the main transport vector for contaminants, so that pathogens and trace metals mainly travel attached to particles through adsorption and biding processes. The main outcomes and the methodology applied in this research will be transferable to intensely karstified areas worldwide where karst groundwater represents the main water source for urban development.
Keywords: Karst - Andalucía; Contaminación - Análisis; Karst; Contaminación; Ubrique